(untitled) (Journal of the College of Education for Women, 2019)
Abstract:This research to monitor the features of the historical method in thethought of a linguistic scientist is known (ibin genieD. 392 AH by offering arange of grammatical rules presented in his book (the properties and thenature of their treatment on the basis of the historical method in accordancewith These are an important milestone in facilitating the grammatical rules anddisplay image "makes it more suitable for the social reality